Depois do Modernismo (= After Modernism). - Barrias, José; Basto, Jwow; Fernandes, José Manuel; Lapa, Alvaro; Moura, Leonel; Pereira, Michel Alves; Pinto, Cerveira; Serpa, Luis; Serpa, Safira; The Executive Committee; Vasconcelos, Helena (Lisboa, 1983)
Oliveira, Alberto de Souza ; Gomes, Candido Chuva ; Salvador, Fernando Sanchez ; Nunes, Margarida Grácio ; Vasconcelos, Joao ; Caldas, Joao Vieira ; Braizinha, Joaquim ; Almendra, Teresa ; Fernandes, José Santa Rita ; Fernandes, José Manuel ; Santos, Miquel Chalbert ; Leal, Tomás D'Eça ; Braga, António Maria ; Consiglieri, Victor ; Tenreiro, Adalberto ; Ferreira, António Barreiros ; Gomes, Candido Chuva ; Lima, António Belém ; Miguel, António Marques ; Alves, Bernardo Daupias ; Evangelista, Cardim ; Macedo, Carlos Lemonde ; Marques, Carlos ; Lameiro, Carlos Silva ; Travassos, Carlos ; Salvador, Fernando Sanchez ; Nunes, Margarida Grácio ; Braizinha, Joaquim ; Almendra, Teresa ; de Graça, Joao Carrilho ; Paciencia, Joao ; Vasconcelos, Joao ; Caldas, Joao Vieira ; Pinto, Jorge Farelo ; Monteiro, José Charters ; Fernandes, José Santa Rita ; Oliveira, Alberto de Souza ; Venade, M.a Rosário ; Caldeira, José Manuel ; Grilo, Júlio Teles ; Teles, Luis Lourenço ; Cunha, Luis ; Machado, Luis Sá ; Fernandes, José Manuel ; Bastos, Manuel ; Dias, Manuel Graça ; Lacerda, Manuel ; Barracas, M.a do Céu ; Almeida, M.a Manuel Godinho ; Pereira, Michel Alves ; Costa, Luis Patricio ; Santos, Miguel Chalbert ; Real, Troufa ; Mestre, Victor ; Vicente, Manuel ; Ferreira, Vicente Bravo ; Consiglieri, Victor ; Dias, Adalberto ; Soutinho, Alcino ; Costa, Alexandre A. ; Siza, Alvaro ; Tavares, Domingos ; Moura, Eduardo Soutto ; Fernandez, Sérgio ; Sarmento, Julião ; Arizona ; Lapa, Alvaro ; de Sousa, Angelo ; Palolo, Antonio ; Pinto, Cerveira ; Gaetan ; Barrias, José ; de Carvalho, José ; Basto, Jwow ; Moura, Leonel ; Serpa, Luis ; Robalo, Lurdes ; Varela, Mário ; Calapez, Pedro ; Pinto, Rocha ; Pombo, Sergio ; Pomar, Vitor
biografie
Portugees
Portugees & Engels
boek